PENGARUH PENDAPATAN ASLI DAERAH DAN PENDAPATAN TRANSFER TERHADAP HUBUNGAN ANTARA BELANJA MODAL DENGAN BELANJA PEMELIHARAAN DALAM ANGGARAN DAERAH - Mochammad Solichin (Optimum: Jurnal Ekonomi dan Pembangunan, 2015)
Objective of this study is to empirically test whether local original incomeand transfer revenue give infl uence to the relation between capital expenditure andmaintenance expenditure in regional government budget. First test showed that reallocal original income give positive effect toward this relation in present year andmaintenance expenditure in next year. This result shows that real local original incomeis considered variable by local government in arranging budget of maintenance inrelation with capital expenditure policy. Second test showedthat transfer revenue haveno positive effect to the relationship between present year capital expenditure andmaintenance expenditure in next year. This result explaining that transfer revenue isnot considered variable during determination of next year maintenance expenditureby local government in relation with present year capital expenditure. This study giveempiric evidence of fl ypaper effect in relation between revenue and regional budget,which suggests that people tend to be effectively spend their revenue that comes fromtheir own effort, than income from other party.